Prevalence of diagnosed and undiagnosed diabetes mellitus in adults aged 19 years and older in Basrah, Iraq - Mansour AA (Dove Medical Press, 2014)
Abbas Ali Mansour, Ahmed A Al-Maliky, Bashar Kasem, Abdulsatar Jabar, Khalid Abdulabass MosbehAl-Faiha Diabetes Endocrine and Metabolism Center (FDEMC) Basrah, IraqBackground: Six of the top ten countries in the world with the highest prevalence of diabetes mellitus are in the Middle East. The objective of this investigation was to evaluate the prevalence of diabetes in Basrah, Southern Iraq.Methods: A population-based, cross-sectional, simple random study screened 5,445 persons aged 19–94 years in Basrah, with glycated hemoglobin measured in 88.3% of the population and fasting plasma glucose in 18.7%. Body mass index and other demographic parameters were also measured.Results: Of the 5,445 persons screened, 8.7% had already been diagnosed with diabetes and 11% were found by screening to have undiscovered diabetes, giving an age-adjusted prevalence of diabetes of 19.7%, with 55.7% of those with diabetes being previously undiagnosed. In addition, 29.1% of the screened population had prediabetes, giving a prevalence of dysglycemia of 48.8%, with only 51.2% of the persons screened being normoglycemic. The prevalence of diabetes in both sexes peaked at age 46–60 years. Diabetes was slightly more prevalent in females than in males, and about 70.3% of diabetic individuals had a body mass index ≥25 kg/m².Conclusion: The prevalence of diabetes in Basrah, Iraq, is very high, affecting one in five adults. The epidemic of diabetes will result in strain on the financial resources of health care systems.Keywords: diabetes mellitus, screening, epidemiology, glycated hemoglobin, Iraq